Acute cerebellar ataxia: A rare association of hepatitis a infection - Shweta Sharma; Prithivi R Prakash; Ananthu Narayan; Ajay Garg; Naveet Wig (Annals of Indian Academy of Neurology, 2023)
Acute cerebellar ataxia (ACA) is a self-limited syndrome that is frequently post-infectious, most commonly following Varicella infection having an autoimmune mechanism. ACA is the commonest cause of childhood ataxia. We report a 14-year-old male who presented with acute onset wide-based gait and slurring of speech with dysdiadochokinesia, incoordination of voluntary movements, pendular knee jerk, and intentional tremors. He had worsening transaminitis and rising bilirubin during his hospital course and was subsequently found to be hepatitis A virus (HAV) immunoglobulin-M antibody positive. Thus, we report a case of ACA with HAV infection who developed jaundice after three weeks of onset of ataxia, a rarity that has not been reported so far in medical literature.